دور العامل السياسي في خدمة المذهب الاشعري في مصر الايوبية (576-648 ه / 1171-1250م ) - بن احمد سارة; د/ جعيرن حنان (جامعة عمار ثليجي الاغواط, 2024)
ملخصالدراسة: العقيدة الأشعرية أو الأشاعرة سمية نسبة إلى مؤسسها أبو الحسن الأشعري توفي في بغداد سنة 324ه، تتلمذ على يد أساتذه أبي علي الجبائي شيخ المعتزلة وقد نبغ الأشعري في علوم المعتزلة واشتهر بقوة الجدال والمناظرة وقد كان أبو الحسن الأشعري في بدايته معتزلاً ودافع عن آرائهم وناصر التأويل العقلي وناظر في الفكر الاعتزالي ولما بلغ سن الأربعين انقلب على المعتزلة وشنا عليهم حملة مؤكدًا من ضرورة التمسك بكتاب الله وسنة الرسول صلى الله عليه وسلمولقد اعترف بنفسه أمام الملأ وأشهد الناس عليه كونه تبرأ من الاعتزال، وإذ خلع عما كان يعتقده من قبل ومن الأسباب التي أدت بالأشعري إلى التحول من الاعتزال إلى سنة تنحصر في أشهر من رواية ولعل أرجحها رواية ابن عساكر [إن الأشعري تحير في المسائل التي لم يجد لها جوابًا عند المعتزلة سأل الله أن يهديه إلى الطريق المستقيم. ثم نام فرأى الرسول صلى الله عليه وسلم في المنام فقال له: [عليك بسنتي] وبعد وفاة أبو الحسن الأشعري اشتهر المذهب في الكثير من الدول منها [الدولة الزنكية والسلجوقية] وخاصة في عهد صلاح الدين الأيوبي كانت العودة إلى هوية الأمة المسلمة وإلى عقيدة أهل السنة والجماعة من أبرز معالم التجديد في العهد الأيوبي لقد طال الانحراف وانتشرت البدع تحميها دولة ظالمة وهي الدولة الفاطمية بمصر فقد سار صلاح الدين الأيوبي على نهج نور الدين الزنكي في سائر أمور الدولة وتنفيذ العدل فقضي على المظالم واعتمد في ذلك على القضاة والفقهاء وقام صلاح الدين الأيوبي بترسيخ دولته بعقيدة أهل السنة والجماعة التي بينها الرسول صلى الله عليه وسلم وسار على نهجها الخلفاء الراشدين حتى حارب صلاح الدين المذهب الشيعي ومحاربة العقائد الفاسدة في مصر وإعادة الفكر الإسلامي الصحيح إليها عن طريق بناء مدارس وتعيين علماء لتدريس المذهب وإلغاء الأذان الشيعي واستبداله بالأذان السني انتصر الأيوبيين بعد وفاة صلاح الدين الأيوبي على هذه العقيدة والعمل على نشرها. Study summary The Ash'arite or Ash'ari doctrine is named after its founder, Abu al-Hasan al-Ash'ari. He died in Baghdad in the year 324 AH. He studied under his teachers, Abu Ali al-Jabba'i, the sheikh of the Mu'tazila. Al-Ash'ari excelled in the sciences of the Mu'tazila and was famous for the strength of debate and debate. Abu al-Hasan al-Ash'ari, in his early days, was a Mu'tazila and defended their opinions and championed rational interpretation. He examined the Mu'tazila thought, and when he reached the age of forty, he turned against the Mu'tazilites and launched a campaign against them, emphasizing the necessity of adhering to the Book of God and the Sunnah of the Messenger, may God bless him and grant him peace. He confessed himself in public, and people bore witness to him because he disavowed the Mu'tazila, and as he renounced what he had previously believed and the reasons that led to According to Al-Ash’ari, the shift from the Mu’tazila to a Sunnah is confined to a few months of narration, and perhaps the most likely of them is the narration of IbnAsakir [Indeed, Al-Ash’ari was perplexed by the questions for which he did not find an answer among the Mu’tazilites. He asked God to guide him to the straight path. Then he fell asleep and saw the Messenger, may God bless him and grant him peace, in a dream and said to him: [You must adhere to my Sunnah]. After the death of Abu Al-Hasan Al-Ash’ari, the doctrine became famous in many countries, including [the Zengid and Seljuk state], especially during the era of Saladin Al-Ayyubi. There was a return to the identity of the Muslim nation and to the doctrine of the Sunnis. The community is one of the most prominent features of renewal in the Ayyubid era. Deviation has been prolonged and heresies have spread, protected by an unjust state, which is the Fatimid state in Egypt. Saladin al-Ayyubi followed the approach of Nour al-Din al-Zenki in all matters of state and the implementation of justice. He eliminated injustices and relied on judges and jurists in this regard. Saladin al-Ayyubi established His state was based on the doctrine of the Sunnis and the community, which was explained by the Messenger, may God bless him and grant him peace, and which the Rightly Guided Caliphs followed until Saladin fought the Shiite doctrine and fought the corrupt doctrines in Egypt and restored correct Islamic thought to it by building schools and appointing scholars to teach the doctrine and abolishing the Shiite call to prayer and replacing it with the Sunni call to prayer. The Ayyubids were victorious after The death of Saladin Al-Ayyubi led to this doctrine and work to spread it.